THE USE OF ENGLISH TEACHER REPETITION IN THE CLASSROOM INSTRUCTION - Marzuki, Mutmainnah (Fakultas Keguruan dan Ilmu Pendidikan, 2016)
The objectives of the research were to find out the function and the types of English teacher repetition in the classroom interaction and it focused on the psycholinguistic discipline. Based on the Tannen (2007) theory there are six types of repetition, they are (1) participatory listenership, (2) ratifying listenership, (3) humor, (4) savoring, (5) stalling, and (6) expanding. In another side that Tannen (2007) categorize the function of repetition they are (1) production, (2) comprehension, (3) Connection, (4) interaction. The results of the research are just some of types that teacher used in the classroom interaction, they are: participatory and ratifying listenership, it means that the students receive and understand what the teacher said and when the speaker says several words and it could be repeated by the listener just a part of the speaker’s words or the speaker incorporates the repeated phrases into their own sentence. About the functions are just production and connection.